Artesanato como exemplo de trabalho informal em uma região econômica periférica: uma análise geográfica do aglomerado produtivo de palhas e bordados da região norte do Piauí - Lima, Naíla Kelly do Nascimento [UNESP] (2015)
The lack of formal employment in localities with low economic growth and the existence of residents with lower level of education than labor market demands are factors that, linked to the need for survival, have resulted in constant increase search for informal and low-paid employment. This reality was observed through the study of the handicraft in North of Piauí, mainly using straw and needlework, due to the large amount of material available in nature and cultural tradition, passed through generations by diffusion of tacit knowledge. For being a significant economic activity in the region due to the income generation for hundreds of artisans and their families, usually beneficiaries of the social government program Bolsa Família, it had Federal and State government support from the 2000s, creating the most productive handicraft agglomeration of Piauí. Therefore, the developed research aimed to analyze the specifics of productive labor dynamics in the handicraft agglomeration production of North Piauí, focusing on informality. The research, carried out with the artisans and the presidents of the work associations, revealed that production output is almost entirely domestic, mainly by female work with family members help. Because it is an informal practice, the workers don‟t have labor rights, as fixed salary, retirement rights, vacation, accident insurance etc. Nowadays the absence of cooperation among the associations and the lack of technical support, managerial and financial, by public and private institutions prevent efficient governance and make the results fall short of the production capacity of artisans and the amount of material available in the region. As a result, the handicraft activity cannot be the only source of income, which leaves them economically vulnerable and keeps them subjugated by government assistance programs